Mediterranean diet rich in olive oil and obesity, metabolic syndrome and diabetes mellitus - Pérez-Martínez, Pablo; García-Ríos, Antonio; Delgado-Lista, Javier; Pérez-Jiménez, Francisco; López-Miranda, José (Current pharmaceutical design, 2011)
After decades of epidemiological, clinical and experimental research, it has become clear that consumption of Mediterranean dietary patterns rich in olive oil has a profound influence on health outcomes, including obesity, metabolic syndrome (MetS) and diabetes mellitus. Traditionally, many beneficial properties associated with this oil have been ascribed to its high oleic acid content. Olive oil, however, is a functional food that, besides having high-monounsaturated (MUFA) content, contains other minor components with biological properties. In this line, phenolic compounds have shown antioxidant and antiinflammatory properties, prevent lipoperoxidation, induce favorable changes of lipid profile, improve endothelial function, and disclose antithrombotic properties. Research into the pharmacological properties of the minor components of olive oil is very active and could lead to the formulation of functional food and nutraceuticals. Although more data are mandatory the Mediterranean diet rich in olive oil does not contribute to obesity and appears to be a useful tool in the lifestyle management of the MetS. Moreover there is good scientific support for MUFA diets, especially those based on olive oil, as an alternative approach to low-fat diets for the medical nutritional therapy in diabetes. The objective of this review is to present evidence illustrating the relationship between Mediterranean diet, olive oil and metabolic diseases, including obesity, MetS and diabetes mellitus and to discuss potential mechanisms by which this food can help in disease prevention and treatment.